2006
DOI: 10.1113/expphysiol.2006.033217
|View full text |Cite
|
Sign up to set email alerts
|

Histamine mediates osteoclastic resorption only during the acute phase of bone loss in ovariectomized rats

Abstract: Short-term studies have shown that histamine is involved, via its H 2 receptors (H 2 R), in the mediator network regulating trabecular bone loss in long bones of ovariectomized (OVX) rats. It is not known whether this effect of histamine persists over time or involves other skeletal sites. In this study, rats were maintained for 6 months postOVX and treated daily with saline or famotidine (10 mg kg −1 ), an H 2 R antagonist. At the end of the experimental period, femur trabecular bone mass was markedly decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Bone loss is known to be associated with mastocytosis, in which excess release of histamine enhances bone remodeling 19. Estrogen's effect on bone health may be partly related to histamine; estrogen depletion directly stimulates histamine release from mast cells and increases bone resorption through osteoclastogenesis 17, 20. Our observation of an increment in bone density in H1RA users suggests that histamine blockade by H1RA may protect against osteoporosis.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Bone loss is known to be associated with mastocytosis, in which excess release of histamine enhances bone remodeling 19. Estrogen's effect on bone health may be partly related to histamine; estrogen depletion directly stimulates histamine release from mast cells and increases bone resorption through osteoclastogenesis 17, 20. Our observation of an increment in bone density in H1RA users suggests that histamine blockade by H1RA may protect against osteoporosis.…”
Section: Discussionmentioning
confidence: 77%
“…Animal studies suggested that histamine is involved in the early phase of bone destruction,18, 20 and that decreased osteoclastic activation by H1RA may not last long. 28 Along with the fact that the protective effect of histamine antagonists against femoral bone loss did not last more than 6 months after the beginning of the treatment, 20 our observation also suggests that the inhibitory effects of these medications on bone loss may not persist for over time.…”
Section: Discussionmentioning
confidence: 99%
“…(38,39) To date, studies have emphasized the role of mast cell–derived histamine in osteoclastogenesis and bone resorption. (4044) The role of mast cells in osteoblast differentiation and HPT-induced bone marrow fibrosis has received less attention.…”
Section: Discussionmentioning
confidence: 99%
“…Famotidine decreased orthodontic tooth movement and the gene expression level of histamine H 2 receptors increased during the late stage of orthodontic tooth movement. Histamine H 2 antagonists have been shown to prevent osteoclastic bone resorption [2,7]. According to these results, histamine could play a role via the H 2 receptors during the late stage of orthodontic tooth movement in rats.…”
Section: S32mentioning
confidence: 93%
“…Many mediators are involved in that process [1], histamine is probably one of them. It is involved, via histamine H 2 receptors in regulating trabecular bone loss in long bones of ovariectomized rats [2]. The aim of the study was to determine the infl uence of famotidine, a histamine H 2 receptor antagonist, on orthodontic tooth movement in rats.…”
Section: Introductionmentioning
confidence: 99%